Doing Without the Active Intellect: Abū l-Barakāt al Baghdādī and Fakhr al-Dīn al-Rāzī Against Ibn Sīnā. - Adamson, Peter; Noble, Michael Sebastian (Monist, 2025)
This paper looks at critiques of the notorious doctrine of the Active Intellect, first introduced by al-Fārābī and further developed by Ibn Sīnā (Avicenna). The Active Intellect plays two roles in Ibn Sīnā's thought. First, it somehow facilitates human thinking. Second, it provides form to suitably prepared matter to produce natural substances. Among later critics of this doctrine, particularly significant were Abū l-Barakāt al Baghdādī and Fakhr al-Dīn al-Rāzī, who proposed that the same functions could be played by other causes, for instance celestial souls. The also paper contextualizes these objections within their broader philosophical commitments, for instance to the idea that humanity is divided into numerous "subtypes" that might each have their own celestial cause.